The Effects of Kombucha Extract Cream in Modulating EGF and IL-10 Levels in Xerosis-Like Model - Wina Shaulla Polnaja; Sri Priyantini Mulyani; Siti Thomas Zulaikha (Cell and BioPharmaceutical Institute, 2026)
Background: Xerosis leading to chronic pruritus and increased inflammation. Current treatment like urea, may induce itching, burning and stinging sensations in some patients. Kombucha extract exhibits antioxidant, anti-inflammatory, and moisturizing properties; however, evidence on the effects of green tea kombucha extract cream on IL-10 and EGF in xerosis remains limited. This study investigates the effects of kombucha extract cream on epidermal growth factor (EGF) and interleukin-10 (IL-10) represent epidermal generation and inflammation resolution in xerosis-like rat model.Materials and methods: Experimental study employed 30 male Wistar rats divided into five groups, consisting of healthy control (G1), negative control (cream base) (G2), positive control (5% urea cream) (G3), treatment groups receiving 10% (G4) and 20% (G5) kombucha extract cream. Xerosis induction by applying 5% SLS for nine days, topical treatments were applied for seven days. EGF and IL-10 levels were measured from skin tissue using ELISA. EGF data analyzed using One-Way ANOVA and post hoc Tamhane. IL-10 data were analyzed using Kruskal-Wallis and Mann-Whitney (p<0.05).Results: The highest mean EGF levels were observed in G4 (665.96±17.74 ng/L) and the lowest in G3 (573.88±25.09 ng/L). One-Way ANOVA revealed a significant difference in EGF levels across groups (p=0.006). Regarding IL-10 levels, the highest mean was found in G1 (201.41±20.41 pg/mL) and the lowest in G4 (181.60±3.42 pg/mL). The Kruskal-Wallis showed a significant difference in IL-10 levels across treatment groups (p=0.013).Conclusion: Topical 10% kombucha extract cream increased EGF levels and modulated IL-10 in a xerosis-like rat model, highlighting its potential as a topical agent to enhance the skin repair process in xerotic conditions. Keywords: skin barrier repair, EGF, IL-10, topical antioxidant, Wistar rats, sodium lauryl sulfate